The Concept of Prenatal Education Aswaja Annahdliyah's Perspective in Shaping the Character of Early Childhood - Ehwanudin Ehwanudin; Mai Zuniati (Journal of Childhood Development, 2021)
This article concerns prenatal education, which is still less reacted by educational experts. The younger generation has meanwhile started a shift in determining its potential life partner in this millennial era. The aim of this study is therefore to reveal the concept of prenatal training in Aswaja Annahdliya, in the context of library research, in shaping the character of early childhood. This is specifically a series of activities related to library data collection, reading, notes and research material processing. The primary evidence is based on the idea of Aswaja and the concept of Khittah Nahdlilah. He always uses his way of thinking, not extremist and secondary data from expert opinions on the subject. The conclusion of this study is that the implementation of prenatal education needs to be based on Islamic law, namely Alqur and Hadeith as its main source; the opinions of the four Mahzabs from Maliki, Hanafi, Syafi'i, and Hambali, and of Nahdlatul-based muktabaroh books, as long as they are not contradictory with Alquran and existing traditions. This applies to keeping good old traditions and adopting new, more advantageous traditions.